Political bargaining chips: republican internees in Northern Ireland 1972-1975. (2nd April 2020) - Craig, Tony; McCleery, Martin
ABSTRACT: From March 1972 until internment itself was eventually abandoned in December 1975 successive Secretaries of State for Northern Ireland used their powers to arrest and release republican internees. This article demonstrates that several factors contributed to the policy of controlling the arrests and releases of internees, and that the most important was not negotiations with the Provisional IRA (PIRA) but the need to encourage the engagement of moderate nationalists in an emerging political process. The story of internment is often exclusively seen in the narrower narratives of paramilitary historiography and the later 'prison war'. This article adopts a broader contextual approach in which both moderate nationalist, and to a lesser extent, unionist concerns over arrests and releases are considered. In doing so, this work resituates the gradual ending of internment at the heart of the mainstream political discussions in Northern Ireland in the 1970s. The article also contends that this controlled use of internment as a political strategy ultimately proved to be successful for the British government in achieving their desired objectives.